2013
DOI: 10.4314/ajpsy.v16i6.55
|View full text |Cite
|
Sign up to set email alerts
|

Post traumatic stress disorder and resilience in veterans who served in the South African border war

Abstract: Objective: The psychological impact of the South African border war on veterans has received little or no attention. This study determined the prevalence of post-traumatic stress disorder (PTSD), and extent of resilience among a cohort of veterans. Method: Of 1527 former students who matriculated from a Johannesburg high school from 1975 to 1988, only 109 were reachable for convenience and snowballing recruitment into this study. An anonymous, internet-based questionnaire was used to obtain information on demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
3
14
1
Order By: Relevance
“…It is a personality characteristic that enhances individual adaptation and positively influences successful adaptation and coping [ 14 ]. The effects have been well documented for disaster survivors [ 15 ], patients with HIV [ 16 ], war veterans with PTSD [ 17 ], and so on. Researchers assert that personal factors such as resilience [ 15 ] and family support [ 18 ] could explain the differences in mental-health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…It is a personality characteristic that enhances individual adaptation and positively influences successful adaptation and coping [ 14 ]. The effects have been well documented for disaster survivors [ 15 ], patients with HIV [ 16 ], war veterans with PTSD [ 17 ], and so on. Researchers assert that personal factors such as resilience [ 15 ] and family support [ 18 ] could explain the differences in mental-health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Being involved in an armed conflict, a mass casualty situation, a terrorist attack or a natural disaster like an earthquake, changes people. For many of those, these are life changing experiences [22][23][24][25]. This study tried to outline areas of anticipated difficulty in the reintegration experience, and to alert (mental) health practitioners to specific areas that could be problematic.…”
Section: Phasementioning
confidence: 97%
“…Research has shown that between 13 to 32% of combat veterans are likely to experience psychological problems after homecoming [5,6]. Particularly, studies among American and Chinese Dai J, et al [6] Cesur, Sabia & Tekin, South African [2] and Nigerian [7,8] combatants have shown that many military returnees from warzones suffer from posttraumatic stress disorder. In addition to PTSD, studies have also pointed out that exposure to unpleasant combat events can lead to symptoms of depression in military veterans Hoge CW, et al [9] [11], compromised immune system, risky health behaviors, cardiac-related problems, sleep difficulties and general burnout [1].…”
Section: Page 2 Ofmentioning
confidence: 99%
“…Globally speaking, military personnel returning from combat operations are faced with several psychosocial challenges capable of affecting their personal functioning and productivity. In recent times, however, empirical reports have shown astronomical rise in psychological consequences of war among military veterans who return from combat operations [1][2][3]. According to Mirowsky and Ross, psychological distress is a state of emotional suffering characterized by symptoms of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%